PENDAMPINGAN SURVEI KEPUASAN PELAYANAN PUBLIK PADA FASILITAS LIKUIDITAS PEMBIAYAAN PERUMAHAN - Diyanti Diyanti (Program Studi Teknik Sipil Fakultas Teknik Universitas Pancasila, 2024)
It is felt that public services provided by government officials currently do not meet public expectations. This can be seen from various public complaints conveyed through mass media and social networks. If this is not addressed, this will harm the government. The purpose of accompanying the public service satisfaction survey for the Housing Financing Liquidity Facility (FLPP) management activities is an evaluate material for the performance of the Funding Fund Management Center (PPDPP). The method used in this activity is a public service satisfaction survey which refers to the PAN-RB Regulations. The results obtained are that currently, the PPDPP performance for handling FLPP is with a Community Satisfaction Index (IKM) of 3.38, which means the FLPP service provided is in a good category.